Tax Policy and Economic Growth: Does It Really Matter? - Donatella Baiardi; Paola Profeta; Riccardo Puglisi; Simona Scabrosetti (Center for Economic Studies and ifo Institute (CESifo), 2017)
We challenge the “OECD view” (Arnold et al. 2011) according to which a shift from direct to indirect taxation is associated with higher long-run economic growth. We study the relationships between per capita GDP, overall tax revenue and tax composition (in particular direct vs. indirect taxation). We can replicate the findings in Arnold et al. when focusing on the same sample of countries and time period, but not when adopting more cautious estimates of the standard errors. The results are not robust to adding countries and/or extending the time period under consideration. They also differ in the short- and long-run.
Keywords: E62; H20; P50; 330; economic growth; taxation; tax mix; OECD countries